The reality of the process decision-making and their relationship motivated to work "Field study on a sample of principals of secondary schools and their assistants in the province of Lattakia" (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aims at identifying the reality of the decision-making process among the principals of secondary education schools and their assistants in Lattakia governorate and their relation to their motivation to work, and defines the effect of the research variables "type, number of years of experience, educational and educational qualification" on their application to the decision-making process and their motivation to work. In order to achieve the objectives of the research, the researcher constructed a questionnaire to identify the reality of the decision making process, consisting of (23) statements distributed over (3) axes and an open question about the obstacles to the application of the decision-making process, the second to measure motivation of secondary school principals and their assistants towards work consisting of (28) statements distributed over (3) axes, (7) referees from the Faculty of Education, Tishreen University, distributed to a sample of (78) managers and assistant director. The researcher used the descriptive approach to its relevance to the subject of research.The research results showed that the reality of the decision-making process in the secondary schools in Lattakia was medium, that the motivation of the principals and their assistants to work was moderate, and that there was a good correlation between the decision-making process and the motivation of secondary school principals and their assistants to work. And there are no differences between the averages of the sample to determine the reality of decision-making Depending on the gender variable and the existence of differences attributed to the variables of the number of years of experience and qualifications of scientific and educational, and found differences on the determination of motivation towards work by sex and the number of years of experience and scientific qualification and educational. The research also presented several proposals, the most important of which is the organization of training courses for administrators, who are familiar with the steps of the decision-making process and the procedures for its implementation and the promotion of motivation with various incentives.